2018
DOI: 10.1371/journal.pone.0209617
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bud morphology, growth-related genes and nutritional status during cheliped regeneration in the Chinese mitten crab, Eriocheir sinensis

Abstract: During pond culture of Eriocheir sinensis, a high limb-impairment rate restricts the industry development and quality. Therefore, research on limb autotomy and regeneration has important practical significance for the industrial development and basic biology of E. sinensis. This study evaluated the changes in bud morphology, growth-related gene expression and nutritional status during cheliped regeneration in E. sinensis. The study found that the new cheliped was pre-formed in the bud and then regenerated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Chitinase ( CHI ) can hydrolyze chitin in old bones. Therefore, CHI plays an important role in the molting process of E. sinensis [ 34 ]. In this experiment, female E. sinensis 20-E content and mRNA expression levels of RXR and CHI reached their maximum values on August 15, and the mRNA expression level of RXR was higher from August 15 to August 30, which was similar to the change trend of weight gain, weight gain rate, and specific growth rate of female E. sinensis in our previous research results, confirming that the 20-E content was closely related to the growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase ( CHI ) can hydrolyze chitin in old bones. Therefore, CHI plays an important role in the molting process of E. sinensis [ 34 ]. In this experiment, female E. sinensis 20-E content and mRNA expression levels of RXR and CHI reached their maximum values on August 15, and the mRNA expression level of RXR was higher from August 15 to August 30, which was similar to the change trend of weight gain, weight gain rate, and specific growth rate of female E. sinensis in our previous research results, confirming that the 20-E content was closely related to the growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Wang et al (2017), the CPGs are regulated by HR3 and HR4 , and it has been shown that CPG10 may regulate cuticle pressure by activating the ecdysone biosynthesis process. Looking specifically at crustaceans, Zhang et al (2018) showed that the gene expressions of CHT and EcR were significantly upregulated during E. sinensis limb bud regeneration. Although available in all moult stages of juvenile shrimps Fenneropenaeus chinensis , two CHT genes ( FcChi and FcChi‐1 ) showed increased expressions during premoult stage and peaked at late premoult stage (Priya et al 2009).…”
Section: Ecdysone Signalling Pathway and Regulationmentioning
confidence: 99%
“…The involvement of EcR and RXR in protein synthesis of crabs during the regeneration phase is evident based on their high expressions during this phase (Durica et al 2002). For example, limb autotomy resulted in the upregulation of EcR mRNA expression in various tissues of E. sinensis and subsequently promoted limb regeneration and moulting (Zhang et al 2018). It was noted that the concentration of EcR mRNA shows slight reduction at the end of proecdysis and right before the next moult in fiddler crab Uca pugilator (Chung et al 1998).…”
Section: Ecdysone Signalling Pathway and Regulationmentioning
confidence: 99%
“…Specialized biological traits (ability to rapidly regulate: body fluid osmolality, cellular volume in the gill lamellae and gene expression) present in crabs (also broadly across the crustaceans that exhibit spawning migrations) are believed to be the main driving force for their ability to tolerate wide-ranging salinities (Lv et al, 2019;Rahi, Mather, Ezaz, & Hurwood, 2019;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ionic balance is the major problem for any aquatic organisms if environmental salinity levels changes (Freire, Onken, & McNamara, 2008; Lv et al., 2013; Moshtaghi, Rahi, Mather, & Hurwood, 2018; Rahi, Amin, Mather, & Hurwood, 2017). Specialized biological traits (ability to rapidly regulate: body fluid osmolality, cellular volume in the gill lamellae and gene expression) present in crabs (also broadly across the crustaceans that exhibit spawning migrations) are believed to be the main driving force for their ability to tolerate wide‐ranging salinities (Lv et al., 2019; Rahi, Mather, Ezaz, & Hurwood, 2019; Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%